2016
DOI: 10.1038/srep29808
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Persulfide Site Identification (qPerS-SID) Reveals Protein Targets of H2S Releasing Donors in Mammalian Cells

Abstract: H2S is an important signalling molecule involved in diverse biological processes. It mediates the formation of cysteine persulfides (R-S-SH), which affect the activity of target proteins. Like thiols, persulfides show reactivity towards electrophiles and behave similarly to other cysteine modifications in a biotin switch assay. In this manuscript, we report on qPerS-SID a mass spectrometry-based method allowing the isolation of persulfide containing peptides in the mammalian proteome. With this method, we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 61 publications
2
68
0
Order By: Relevance
“…6g). These results suggest that H 2 S inhibits ubiquitously cellular antioxidant enzymes that rapidly consume H 2 O 2 , such as peroxiredoxins and GSH peroxidases, most likely via the formation of Cys persulfides that affect the activity of target proteins69. Regardless, these observations do not provide any information regarding the heme-iron species accountable for SpCAT inhibition in cancer cells and rotenone-treated BE2-M17 cells.…”
Section: Resultsmentioning
confidence: 78%
“…6g). These results suggest that H 2 S inhibits ubiquitously cellular antioxidant enzymes that rapidly consume H 2 O 2 , such as peroxiredoxins and GSH peroxidases, most likely via the formation of Cys persulfides that affect the activity of target proteins69. Regardless, these observations do not provide any information regarding the heme-iron species accountable for SpCAT inhibition in cancer cells and rotenone-treated BE2-M17 cells.…”
Section: Resultsmentioning
confidence: 78%
“…Proteins with vicinal thiols (like roGFP2) can rapidly convert hydropersulfide groups to disulfides, but other proteins may acquire the hydropersulfide as a more stable modification. Indeed, protein hydropersulfidation seems to be relatively common as a detectable posttranslational modification (Doka et al, 2016; Gao et al, 2015; Longen et al, 2016; Wedmann et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…An advantage of this method compared to others developed previously is that it utilized an alkylation step prior to cellular lysis, thus precluding cell lysis-mediated artifactual oxidation/persulfidation. Further work by Longen and coworkers [29], also using a mass spectrometry-based assay (entitled quantitative PerSulfide Site Identification or qPerS-SID), found that cells treated with H 2 S resulted in the generation of numerous protein hydropersulfides (with significant identification overlap with the above-mentioned work by Ida and coworkers [27]). They also found that H 2 S-mediated protein hydropersulfide formation appeared to exhibit specificity among numerous potential "sulfhydration" sites.…”
Section: The Generation and Prevalence Of Hydropersulfides And Polysumentioning
confidence: 93%